UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI PENGGUNAAN METODE DISKUSI PADA SISWA KELAS VII MTs. MUHAMMADIYAH MARGOTOTO TAHUN PELAJARAN 2011/2012 - Muqosim Muqosim; Anak Agung Oka (UNIVERSITAS MUHAMMADIYAH METRO, 2013)
The purpose of this study were to increase the biological activity and learning outcomes through the discussion method. In the theory, discussion method is a method in the learning process so that students dare to issue his opinion, daring to ask and answer questions. The analysis of data showed an increase in activity and student learning outcomes. The research was conducted at grade VII MTs. Muhammadiyah Margototo academic year 2011/2012. Expression increased the activity of 10.29%, the activity of your friends pay attention when presenting the results of their discussion to increase 24.02%, the activity increased 11.27% to ask questions, answer questions activity increased 16.67% and complete the task group activities increased 19.52%. On learning outcomes also increased with evidence of students increased to 24% complete. Kata Kunci: Diskusi, Aktivitas Belajar, Hasil Belajar.